Monoamine Oxidases, Oxidative Stress, and Altered Mitochondrial Dynamics in Cardiac Ageing. (4th May 2017) - Maggiorani, Damien; Manzella, Nicola; Edmondson, Dale E.; Mattevi, Andrea; Parini, Angelo; Binda, Claudia; Mialet-Perez, Jeanne
Abstract : The advances in healthcare over the past several decades have resulted in populations now living longer. With this increase in longevity, a wider prevalence of cardiovascular diseases is more common and known to be a major factor in rising healthcare costs. A wealth of scientific evidence has implicated cell senescence as an important component in the etiology of these age-dependent pathologies. A number of studies indicate that an excess of reactive oxygen species (ROS) contributes to trigger and accelerate the cardiac senescence processes, and a new role of monoamine oxidases, MAO-A and MAO-B, is emerging in this context. These mitochondrial enzymes regulate the level of catecholamines and serotonin by catalyzing their oxidative deamination in the heart. MAOs' expression substantially increases with ageing (6-fold MAO-A in the heart and 4-fold MAO-B in neuronal tissue), and their involvement in cardiac diseases is supposedly related to the formation of ROS, via the hydrogen peroxide produced during the substrate degradation. Here, we will review the most recent advances in this field and describe why MAOs could be effective targets in order to prevent age-associated cardiovascular disease.